MEKANISME KOORDINASI GUGUS TUGAS PERCEPATAN PENANGANAN COVID-19 DALAM PENANGGULANGAN PANDEMI COVID-19 DI KABUPATEN X PROVINSI SUMATERA BARAT - Z.A. Prima Putri; Syahirul Alim; Dwi Handono Sulistyo (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2022)
Background: Coordination is key to the success of disaster management when many parties are involved. However, in carryingout coordination in District X, it is known that there are obstacles, so coordination has not run as it should.Objective: This study aims to explore cross-sectoral coordination (COVID-19 Response Acceleration Task Force) in dealing with theCOVID-19 pandemic in the X Regency. Methods: This is qualitative descriptive research with seven informants from BPBD and X District Health Office. Data was collected through in-depth interviews with transsectional data collection, which only captures the situation at a specific time of the entire longitudinal phase of the disaster, precisely when the COVID-19 Omicron variant developed. Data validation was done by triangulation of sources. Results: The mutual adjustment mechanism has been made by holding meetings to discuss developing issues and compiling. In addition, non-formal communication is also carried out through Whatsapp groups. The direct supervision mechanism carried out by the head of the task force is monitoring and evaluation based on reporting in each implementing field through in-person or online meetings. The process of standardisation mechanism was not carried out because the activities within the task force were deemed to have been integrated with the duties of each regional apparatus institution, so it was sufficient to refer to the guidelines that had been prepared at the central level as a form of standardised activity. Conclusion: The dominant coordination mechanism carried out during the COVID-19 pandemic disaster by the task force in X Regency was mutual adjustment and direct supervision.